Mechanism, Implementation, and Challenges in Independent Campus Education Policy in Indonesia - Deding Ishak (International Journal of Science and Society, 2021)
The Independent Learning-Independent Campus Policy was issued by the Minister of Education and Culture of the Republic of Indonesia, Nadiem Anwar Makarim. The policy aims to improve the competence of graduates, both soft skills and hard skills, to be more prepared and relevant to the needs of the times, to prepare graduates as future leaders of the nation with excellent and personalities. "Freedom of Learning, Independent Campus" policy includes the opening of new study programs, a higher education accreditation system, the freedom to become a PTN-BH, and the right to study for three semesters outside the study program. This policy of the Minister of Education and Culture deserves to be called a reasonably extreme change. This then raises some doubts in the minds of academics. The method used by the author in this study is a literature study approach. In this method, data is collected through a literature study, analyzed, and presented in the discussion. The study results show that the visionary policy of the Minister of Education and Culture deserves to be appreciated. Still, several problems arise from implementing the "Independent Learning, Independent Campus" policy that must be immediately resolved.